EIS: the scattering beamline at FERMI. (7th April 2015) - Masciovecchio, Claudio; Battistoni, Andrea; Giangrisostomi, Erika; Bencivenga, Filippo; Principi, Emiliano; Mincigrucci, Riccardo; Cucini, Riccardo; Gessini, Alessandro; D'Amico, Francesco; Borghes, Roberto; Prica, Milan; Chenda, Valentina; et al.
<x xml:space="preserve">Abstract</x> The Elastic and Inelastic Scattering (EIS) beamline at the free‐electron laser FERMI is presented. It consists of two separate end‐stations: EIS‐TIMEX, dedicated to ultrafast time‐resolved studies of matter under extreme and metastable conditions, and EIS‐TIMER, dedicated to time‐resolved spectroscopy of mesoscopic dynamics in condensed matter. The scientific objectives are discussed and the instrument layout illustrated, together with the results from first exemplifying experiments.